Efeitos do método mãe-canguru sobre o desenvolvimento motor de bebês pré-termo extremos. - Canotilho, Marta Martins (2005)
The Kangaroo Mother Care (KMC) has been proposed as a new model of neonatal intervention. This study aimed to contribute for the comprehension of the KMC as a neonatal intervention to promote the motor development of extremely preterm babies. The objectives of this study were (1) to compare the effects of the KMC in motor development between extremely preterm babies and preterm babies of larger gestational ages, (2) to characterize the motor development of extremely preterm babies submitted to the KMC, comparatively of the preterm babies submitted to the traditional routine, (3) to analyze possible relations between the motor development of extremely preterm babies and components of the KMC, as contact skin-to-skin, maternal breast-feeding and the mothers care of their babies until discharge. Participants were 12 at term babies and 66 preterm babies, allocated in 3 groups: the control group 1 (GC1), subdivided in a group of 15 babies with less of 32 weeks of gestational age (GC1<32s) and another of 19 babies with age gestational between 32 and 36 weeks (GC1≥32s), the kangaroo-mother group (GMC) submitted to the KMC during the diurnal period, since the clinical stability up to hospital discharge, subdivided in a group of 15 babies with less of 32 weeks of age gestational (GMC<32s) and another of 17 babies with age gestational between 32 and 36 weeks (GMC≥32s), and the group control 2 (GC2), with 12 babies at term. The motor development was evaluated longitudinally with the Alberta Infant Motor Scale (AIMS), monthly to the 6 months and afterwards to the 9, 12, 14 and 16 months of age (corrected for the preterm baby). The babies of the GC1<32s presented motor development delay, especially in the first semester of life. The babies of the GC1≥32s, GMC<32s, GMC≥32s and GC2 did not present differences in the motor development. The KMC favored the motor development of extremely preterm babies, matching their motor development to the at term babies. The breastfeeding correlated positively with larger punctuations in the scale AIMS in the extremely preterm babies to the 3 and 6 months of age. The mothers care of their babies until discharge correlated positively with larger punctuations in the scale AIMS in the extremely preterm babies to the 6 months of age. The variability of the exposition to the skin-to-skin contact (between 74 and 255 hours) was not associated with the variability of the punctuations in the scale AIMS, in the first year of life. The KMC is a neonatal intervention model to promote the motor development of extremely preterm babies during the first months of life and contributed to humanize the hospital care, to capacitate the mothers in the care of their babies, and to promote the breastfeeding.